Contacts between the Cistercian Monks and the Christians of the Eastern Rite between the 12th and 13th Centuries - Todika, Raul-Alexandru (Review of ecumenical studies, 2023)
The Order of Cistercians was one of the most powerful tools employed by the Apostolic See in order to impose its hierocratic vision as well as its disciplinary regime and to forge the institutional, religious coherence of Christianitas during the 12th and 13th centuries. The main objective of this paper is to bring forward a problematization concerning the Cistercians acting as a means of evangelization in the service of Ecclesia Romana in relation to Christians of the Eastern rite. In order to evaluate this hypothesis, the present article emphasises the perception of the Holy See in regard to the elements external to Latin Christianity, the nature of Cistercian obedience to the Bishop of Rome, and discusses the presence of the White Monks in mediaeval Poland, Banat and Transylvania - border regions of Christianitas where the resurgence of previous beliefs or contacts with the population of the Eastern Christianity matrix were frequent.